1985
DOI: 10.1128/aem.49.4.852-857.1985
|View full text |Cite
|
Sign up to set email alerts
|

Application of flow cytometry to detection and characterization of Legionella spp

Abstract: Flow cytometry, using fluorescein-bound specific antibodies and propidium iodide, was shown to be effective in detecting Legionella spp. in cooling tower waters. The procedure was quicker and less labor intensive than fluorescent microscopy. The use of these procedures also identified qualitative differences, perhaps related to infectivity, in Legionella populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(19 citation statements)
references
References 11 publications
0
18
1
Order By: Relevance
“…From a taxonomic point of view there are not, as far as we know, any studies concerning the taxonomic discrimination of individual components of natural bacteria populations. The only research on the condition of protocols allowing differentiation of taxonomic units (type, species) was carried out on mixtures of pure strains, notably for diagnostic of pathogenic bacteria [14,24,36,50,58]. The determination of the proportions of the bases of DNA (AT/GC), by means of specific fluorochromes (eg AT, Hoechst 33258 and DAPI; GC, chromomycin A3 and mithramycin), would allow the discrimination of certain bacterial species [53].…”
Section: Type Of Study Stain(s) or Method(s) And Reference(s) For Bacmentioning
confidence: 99%
See 1 more Smart Citation
“…From a taxonomic point of view there are not, as far as we know, any studies concerning the taxonomic discrimination of individual components of natural bacteria populations. The only research on the condition of protocols allowing differentiation of taxonomic units (type, species) was carried out on mixtures of pure strains, notably for diagnostic of pathogenic bacteria [14,24,36,50,58]. The determination of the proportions of the bases of DNA (AT/GC), by means of specific fluorochromes (eg AT, Hoechst 33258 and DAPI; GC, chromomycin A3 and mithramycin), would allow the discrimination of certain bacterial species [53].…”
Section: Type Of Study Stain(s) or Method(s) And Reference(s) For Bacmentioning
confidence: 99%
“…However, two organisms that show similar AT/GC ratios are not necessarily identical since these proportions do not take into account the linear arrangement of nucleotides in DNA [25]. The use of monoclonal or polyclonal antibodies [58,62] and nucleic fluorescent probes [2] is a priori certainly more promising. An example of detection of a strain of Salmonella typhimurium identified by means of indirect immunofluorescent staining following the methods of Desmonts et al [12] is shown in figure 2.…”
Section: Type Of Study Stain(s) or Method(s) And Reference(s) For Bacmentioning
confidence: 99%
“…Flow cytometry (FCM) was already used 30 years ago for Lp detection. These first approaches, however, had very high LODs of 10 4 to 10 6 cells per litre (Tyndall et al, 1985;Lebaron et al, 1998). More recently, FCM-based approaches reached detection limits as low as 500 cells per litre, but high background signals, not well discriminated cell clusters, high counts of false-positives and lacking information about physiological state are some of the drawbacks of these methods (Füchslin et al, 2010;Taguri et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the study of lymphocytes, little work has been done on combining FCM and monoclonal antibodies for the detection of bacteria (Tyndall et al 1985;Phillips and Martin 1988;Nelson et al 1991) and even less using the two for detection in foods (Donnelly and Baigent 1986).…”
Section: Introductionmentioning
confidence: 99%